2013
DOI: 10.1161/hypertensionaha.111.203521
|View full text |Cite
|
Sign up to set email alerts
|

Role of T Regulatory Lymphocytes in the Pathogenesis of High-Fructose Diet–Induced Metabolic Syndrome

Abstract: Abstract-We recently showed that T regulatory lymphocytes (Treg), which are immune suppressors of inflammatory responses, play a role blunting the development of hypertension-induced injury. Treg are unchanged or decreased in children with metabolic syndrome, and therefore, their role in metabolic syndrome remains unclear. We hypothesized that Treg number or function would be depressed in a high-fructose diet-induced metabolic syndrome-like model in rats. Sprague-Dawley rats were fed normal chow or a high-fruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 48 publications
2
28
0
4
Order By: Relevance
“…21,22 Our findings extend these observations to fructose-fed rats, which show similar metabolic disturbances. 14,23 In the present study, fructose intake caused increased levels of serum norepinephrine, serum triglycerides, insulin, and fasting serum glucose and reduced high-density lipoprotein but resulted in no change in body weight or cholesterol compared with control rats.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…21,22 Our findings extend these observations to fructose-fed rats, which show similar metabolic disturbances. 14,23 In the present study, fructose intake caused increased levels of serum norepinephrine, serum triglycerides, insulin, and fasting serum glucose and reduced high-density lipoprotein but resulted in no change in body weight or cholesterol compared with control rats.…”
Section: Discussionsupporting
confidence: 85%
“…3,24 In particular, most studies have found that administering rats 10% fructose in drinking water induces a more severe metabolic disorder compared with providing 60% fructose in food. 22,24 In this study, we used 10% fructose in drinking water as a fructose-induced hypertension model. Our data revealed the presence of hypertension in fructose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…T regulatory lymphocytes suppress inflammatory responses and attenuate hypertension-associated organ damage. It was reported that high fructose diet-induced metabolic syndrome decreased the number and function of the T regulatory lymphocytes, 27 which may promote metabolic syndrome-associated arterial stiffening and hypertension.…”
Section: Inflammation Mediates Aging-related Arterial Stiffening and mentioning
confidence: 99%
“…92 In contrast, T regulatory cells, which are immune suppressors having anti-inflammatory activity, are decreased in angiotensin II-induced hypertension and high-fructose diet-induced metabolic syndrome. 88,97 A recent study demonstrated that immunosenescent CD8 + T cells are increased in human hypertension. 98 Thus, low-grade inflammation and oxidative stress play a role in above-mentioned abnormalities, including the brain mechanisms of hypertension.…”
Section: Low-grade Inflammations and Immunitymentioning
confidence: 99%